Civic Education and Pupils’ Civic Dispositions in Ghana and Nigeria: A Comparative Analysis - Odusanya, Sunday Paul; Oni, Adesoji (Journal of Education and Research, 2019)
The ultimate desire of any sensitive government is to build responsible citizens who will participate meaningfully in the developmental efforts within and outside society. The current social-political upheavals in Ghana and Nigeria underscored the need for national value orientation and reorientation for effective nation-building. The study adopted a descriptive survey to assess gender differences in pupils’ civic disposition in Ghana and Nigeria. A multistage sampling procedure was used to select 920 Basic 8 pupils from four educational circuits in Central Region, Ghana and four Local Government Education Authorities in Lagos and Ogun State in South-West, Nigeria. The research tool was tagged: Basic Education Pupils’ Questionnaire (BEPQ). The data were analysed using simple percentages, mean scores and independent t-tests at 0.05 level of significance. The results showed that there is no significant gender difference in the contribution of basic education to pupils’ civic disposition. The main conclusion drawn from this study is that the difference in the level of civic awareness of basic school pupils is due to the quality of basic education and that civic disposition increases the likelihood of a person engaging in civic activities. Government at all levels should encourage publication of relevant textbooks and research findings on basic school pupils especially in value-laden subjects like civic education.